Development of Non-Conventional Energy Systems as a Source of Electric Power for Alternators - PARTAONAN HARAHAP; RIMBAWATI RIMBAWATI; CHOLISH CHOLISH; ABDULLAH ABDULLAH; JOKO ARIF SETIAWAN (Institut Teknologi Nasional, Bandung, 2025)
This Development of a Non-Conventional Energy System as a Power Source for an Alternator aims to design an efficient and self-sustaining power generation system. The study focuses on the drive mechanism, rotor speed synchronization, and excitation current analysis to achieve optimal electrical output. Experimental results indicate peak performance at 4000 RPM with an induced voltage of 1539 V (star configuration) and a rectified DC output of 14 V. An excitation current of 7 A produced an electromagnetic torque of 2.44 Nm, ensuring stable operation. The developed system demonstrates efficiency, stability, and potential for future energy-independent vehicle applications.